The customer education playbook : how leading companies engage, convert, and retain customers - Quick, Daniel; Kelly, Barry (Chief Executive Officer) (Thought Industries, Inc./John Wiley & Sons, Inc., 2022)
"Deliver maximum value to customers and clients with this blueprint to customer success In The Customer Education Playbook: How Leading Companies Engage, Convert, and Retain Customers, customer learning experts Barry Kelly and Daniel Quick explain how teaching customers to best engage with your products and services is the key to converting them from prospects to renewing engagements. In this book, you'll examine how to define success for your customer, create a customer education development plan, and pursue customer success and revenue metrics. You'll also: Learn why you should prioritize customer learning and invest in customer training and education Discover how to create a detailed customer success and retention plan that emphasizes delivered value Determine how to implement a learning strategy that maximizes and scales lifetime customer value Perfect for founders, executives, managers, and practitioners at companies of all kinds, The Customer Education Playbook is especially practical for SaaS company executives seeking to extract and provide maximum value from their customers over the long haul."--